Influence of Ethanol on Emulsions Stabilized by Low Molecular Weight Surfactants. Issue 1 (16th December 2019) - Ferreira, Ana C.; Sullo, Antonio; Winston, Scott; Norton, Ian T.; Norton‐Welch, Abigail B.
Abstract : Abstract: The effect of ethanol on oil‐in‐water emulsions stabilized with low molecular weight surfactants was investigated. Oil‐in‐water emulsions were prepared containing varying percentages of ethanol and sunflower oil, and stabilized with different emulsifiers (Tween 20, Tween 80, and Lecithin). Droplet size, viscosity, density, and interfacial tension measurements were carried out. The droplet size of emulsions stabilized by each of the surfactants studied decreased with the addition of ethanol to the aqueous phase showing a minimum at a concentration of ethanol around 40%. The trend in droplet size is accompanied by a decrease in the interfacial tension between water and oil as the ethanol concentration increases. Viscosity measurements show that the change in viscosity of the final emulsion is the result of the change in viscosity of the continuous phase, as well as the change in solubility of the surfactants due to the addition of ethanol. The density of the continuous phase decreases with the addition of ethanol and it is possible to match the densities of the two phases in order to reduce the effect of creaming/sedimentation and improve stability. This study provides scientific evidence for the formulation of stable emulsions containing a range of ethanol form 0 to 40%. Practical Application: Formation and stability of food‐grade emulsions in the presence of ethanol.